Comprehensive Multimodal Rehabilitation for Chronic Musculoskeletal Problems in Geriatric Patient: A Case Study - Ramadhan, Nanda Aulya; Nugraheni, Nuniek (UNUSA Press, 2024)
Introduction: Musculoskeletal problems are a major cause of morbidity in the geriatric population. These issues can decrease independence, increase functional decline and mortality, and negatively affect the psychological well-being and overall quality of life of elderly individuals. Returning to full function in such cases is highly challenging and requires comprehensive management. Case: A 67-year-old married female housewife presented with sharp, localized chronic pain in her left wrist for one year. The pain was non-radiating, without any tingling sensation, and aggravated by movements such as ulnar deviation and lifting objects (pain scale: 8/10). Tenderness was observed in the lateral anatomical snuffbox of the left wrist, with a positive Finkelstein test. The patient also experienced sharp, localized pain in her left shoulder for seven months following a coronary artery bypass graft (CABG) surgery for coronary artery disease. The shoulder pain worsened with overhead activities (pain scale: 6/10) and improved with rest (pain scale: 3/10). The patient exhibited limited active range of motion (ROM) in flexion, extension, abduction, and external rotation, with positive Neer and Hawkins tests. Her metabolic equivalent of task (METs) score was 3.46, and she scored 5 on the Geriatric Depression Scale. The Barthel Index was 75, and she was diagnosed with several geriatric syndromes: instability (standing balance), impaired vision (cataract), isolation (depression), iatrogenesis (polypharmacy), and impotence (menopause). The patient had difficulties performing daily activities and participating in the community. A multimodal rehabilitation program was implemented, including therapeutic exercise, pharmacotherapy, kinesiotaping, thumb splint, physical modalities, and consultations with an internist and psychiatrist. After several sessions, the patient's pain decreased significantly to 1/10 (wrist) and 0/10 (shoulder). Active ROM improved to near normal, METs increased to 5.27, and she regained full independence in daily activities (Barthel Index 100). Discussion: Chronic musculoskeletal problems, especially when coupled with geriatric syndromes, are particularly challenging to manage. A comprehensive geriatric assessment, combined with a thorough multimodal rehabilitation approach, is key to successful outcomes. Improvements in pain, ROM, depression, and METs can lead to better functional performance, thereby reducing disability and enhancing the patient's quality of life. A supportive caregiver also plays a crucial role in achieving satisfactory results. Conclusions: This case highlights that comprehensive multimodal rehabilitation is crucial for the successful management of chronic musculoskeletal problems in the geriatric population.